[(7x)-(-1)]/-8= (7x+1)/-8=-4 7x+1=32 ... Cross multiplication -1 -1 (7x)/7=31/7 x=31/7 You can check this value for x by plugging it into the original equation [7*(31/7)-(-1)]/-8 (31+1)/-8 32/-8=-4 -4=-4...

7x-(-1)/-8=-4 (answer)

[(7x)-(-1)]/-8= (7x+1)/-8=-4 7x+1=32 ... Cross multiplication -1 -1 (7x)/7=31/7 x=31/7 You can check this value for x by plugging it into the original equation [7*(31/7)-(-1)]/-8 (31+1)/-8 32/-8=-4 -4=-4...

Can you explain this please? Anyone? (answer)

The Pythagorean theorem, a^2+b^2=c^2, is used when you are given a right triangle (a triangle with one right angle) and you are asked to find either side a, b or c (given two sides). Sides a and b are the lengths of any two of the legs (long leg or short leg) and side c represents the length...

S=p/(q+p(1-q)) (answer)

S=p/(q+p(1-q)) by multiplying both the numerator and denominator by 1/(1-q) S=(p*(1/(1-q)))/(1/(1-q))*q+p(1-q)*(1/(1-q)) You can now cancel out common terms to get S=(p/(1-q))/(q/(1-q))+(p(1-q))/(1(1-q)) (the common denominator is(1-q) =(p/(1-q))/(q+p-pq)/(1-q) S/1=(p/(1-q))*((1-q)/(q+p-pq))...

solve for x=8/9x+9=11 (answer)

For the problem x=8/(9x+9)=11 First, you can cross multiply. Then, you get 8=99x+99 (99x+99) comes from distributing the 11 to 9x and to 9 8=99x+99 -99 -99(subtract 99 from both sides of the equation in order to isolate...